2011
DOI: 10.1364/oe.19.004464
|View full text |Cite
|
Sign up to set email alerts
|

Real-time pulse length measurement of few-cycle laser pulses using above-threshold ionization

Abstract: The pulse lengths of intense few-cycle (4-10 fs) laser pulses at 790 nm are determined in real-time using a stereographic above-threshold ionization (ATI) measurement of Xe, i.e. the same apparatus recently shown to provide a precise, real-time, every-single-shot, carrier-envelope phase measurement of ultrashort laser pulses. The pulse length is calibrated using spectral-phase interferometry for direct electric-field reconstruction (SPIDER) and roughly agrees with calculations done using quantitative rescatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 28 publications
0
47
0
1
Order By: Relevance
“…Calibration of the peak intensity on target was done with an estimated precision of 10% by separate measurements using single ionization of argon atoms in circularly polarized light [22]. The duration and intensity stability of the pulses were monitored on a shot-to-shot basis by a stereo-above-threshold-ionization phase meter [23,24]. More details on our experimental setup can be found in our previous publications [9,25,26].…”
Section: Methodsmentioning
confidence: 99%
“…Calibration of the peak intensity on target was done with an estimated precision of 10% by separate measurements using single ionization of argon atoms in circularly polarized light [22]. The duration and intensity stability of the pulses were monitored on a shot-to-shot basis by a stereo-above-threshold-ionization phase meter [23,24]. More details on our experimental setup can be found in our previous publications [9,25,26].…”
Section: Methodsmentioning
confidence: 99%
“…Temporal compression of the pulses after the capillary by several bounces from pairs of chirped mirrors and subsequently passing them through a pair of glass wedges for fine-tuning the dispersion results in a pulse duration of ∼ 4.5 fs. The duration and intensity stability of the pulses are monitored on a shot-to-shot basis by a stereo-abovethreshold ionization phase meter [48,49].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been reported that the stereo-ATI signal alone is sufficient to estimate both the CEP and the duration of the pulses at the same time with the help of quantitative rescattering theory [53][54][55] or calibration with external SPIDER measurements 56 . However, the method is insensitive to the structures below 30% of the peak intensity.…”
Section: Discussionmentioning
confidence: 99%